Blood pressure in Papua New Guinea: a survey of two highland villages in the Asaro Valley. Issue 3 (September 1985) - King, H; Collins, A; King, L F; Heywood, P; Alpers, M; Coventry, J; Zimmet, P
Abstract : The results of a population survey of blood pressure in the adult residents of two highland villages in the Asaro Valley, Papua New Guinea are reported. The survey was conducted in 1983 as part of a wider epidemiological investigation of non-communicable disease in Papua New Guinea. Response to the survey was 95%, and 308 subjects were examined. Population estimates of both systolic and diastolic blood pressures were low and there was a virtual absence of hypertension, as defined by internationally recommended criteria. There was no evidence of a rise in blood pressure with age, and the association between blood pressure and indices of obesity was weak. These findings are consistent with previous studies of blood pressure in traditional Papua New Guinean societies. The two villages differed with respect to their degree of modernisation. An unexpected finding was that in both sexes, both systolic and diastolic blood pressures were higher in the more traditional village. In each case, these differences were consistent across the three age groups examined, and they could not be explained by differences between the villages with respect to the indices of obesity. Analysis of variance showed that the higher blood pressures in the more traditional village were most unlikely to be due to chance (p less than 0.001). The explanation for this finding remains obscure.